QuickBooks 2014 on demand - Long, Michelle (Que Pub., 2014)
Need answers quickly? QuickBooks 2014 on Demand provides those answers in a visual step-by-step format. We will show you exactly what to do through lots of full color illustrations and easy-to-follow instructions. Numbered Steps guide you through each task See Also points you to related information in the book Did You Know alerts you to tips and techniques Illustrations with matching steps Tasks are presented on one or two pages Inside the Book Learn everything you need to know to quickly start using your QuickBooks financial software Produce and customize reports that show exactly how your company is doing Schedule transactions so you'll never forget a due date again Bill time and expenses directly to customers Use the new QuickBooks features for 2014, including Income Tracker, Bank Feeds, and Rules Create and use a budget Reconcile your bank account to the penny without waiting for the bank statement to come in the mail Keep detailed records of fixed asset acquisitions Send customized mailings to your customers and vendors Learn tips and shortcuts to help make your QuickBooks experience more efficient and to customize your program to fit your style Process transactions the right way by following the accounting rules interspersed throughout the book Includes Hundreds of the Most Essential QuickBooks 2014 Tasks Workshops Easy Setup Procedures Reporting Techniques Visit the authors' websites: http://longforsuccess.com http://www.cpapracticeadvisor.com Bonus Online Content Register your book at queondemand.com to gain access to online files such as a video on "Using the Sample Data File."